2020
DOI: 10.1109/access.2020.3014238
|View full text |Cite
|
Sign up to set email alerts
|

Kriging Model for Time-Dependent Reliability: Accuracy Measure and Efficient Time-Dependent Reliability Analysis Method

Abstract: As the performance function of a mechanical structure is usually based on time-consuming computer codes, predicting time-dependent reliability analysis requires a large number of costly simulations in engineering. To reduce the number of evaluations of time-consuming models and enhance efficiency of time-dependent reliability analysis, Kriging is employed as a surrogate of original performance function. Firstly, a quantitative measure of the error of Kriging-based estimation of time-dependent failure probabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…The adaptive sampling method starts from a small experimental design and then sequentially adds the new sample points that contribute the most to the approximate model, thus significantly reducing some unnecessary sample points in the one‐shot experimental design. In the existing surrogate‐based reliability analysis combined with adaptive sampling design, several surrogate models, such as Kriging, 10,11 polynomial chaos expansion (PCE), 12,13 and support vector regression (SVR), 14,15 are frequently used. Kriging is the most popular surrogate model due to its attractive characteristic which can provide both the predicted mean value and variance of unsampled points 16–18 .…”
Section: Introductionmentioning
confidence: 99%
“…The adaptive sampling method starts from a small experimental design and then sequentially adds the new sample points that contribute the most to the approximate model, thus significantly reducing some unnecessary sample points in the one‐shot experimental design. In the existing surrogate‐based reliability analysis combined with adaptive sampling design, several surrogate models, such as Kriging, 10,11 polynomial chaos expansion (PCE), 12,13 and support vector regression (SVR), 14,15 are frequently used. Kriging is the most popular surrogate model due to its attractive characteristic which can provide both the predicted mean value and variance of unsampled points 16–18 .…”
Section: Introductionmentioning
confidence: 99%
“…Next, the cumulative probability of failure is estimated by a random sampling method. The strategies of determining the set of training samples are of the utmost importance for the accuracy and efficiency of surrogate model-based methods, on which a number of studies can be found [36,37]. For example, Jiang et al [38] proposed an active failure-pursuing Kriging method to identify the most valuable samples for improving the accuracy of the Kriging model; Wang et al [37] developed two methods based on projection outline adaptive Kriging to handle time-variant problems with random and interval uncertainties.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with time-independent reliability analysis, timevariant reliability analysis [17] is more in line with the actual situation because the performance of a practical structure or system generally degrades with time. In time-variant reliability analysis, stochastic processes (e.g.…”
Section: Introductionmentioning
confidence: 99%